Static finite element analysis of three-closed box thin-wall beam based on Pseudo-elastic SMA hybrid composite material ANSYS. Issue 2 (March 2021) - Zeng, Lingqi
Abstract: The Auricchio model based on shape memory alloy and the finite element analysis software ANSYS Workbench firstly simulated the pseudo-elastic characteristics of SMA bar during the stretching cycle loading and unloading. Secondly, based on ANSYS Material Designer module, a SMA/glass/epoxy resin composite Material model was established and its Material parameters were obtained. ANSYS ACP module was used to establish the finite element model of pseudo-elastic SMA hybrid composite box thin-walled beam. Finally, the static response of SMA composite box thin-walled beam under transverse load is studied, and the influences of SMA, layout Angle, width to height ratio and volume content of SMA layer on the static response of box girder are discussed. The results show that the transverse displacement of the free end of the thin-walled beam increases with the increase of the laying Angle whether there is SMA fiber or not. After embedding SMA, the transverse displacement of the free end of the box thin-wall beam of hybrid composite was smaller. The transverse displacement of the free end of the thin-walled beam with the change curve of the lay-up Angle under the two con Figurations is consistent and basically consistent. At the same laying Angle, the transverse displacement of the free end of SMA hybrid box thin-walled beam decreases with the increase of the width to height ratio and the volume content of SMA monolayer.